2011
DOI: 10.3892/ol.2011.365
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death 4 (Pdcd4) expression in colorectal adenocarcinoma: Association with clinical stage

Abstract: Abstract. The aim of this study was to examine the role of Programmed cell death 4 (Pdcd4) in colorectal adenocarcinoma (CRA). Pdcd4 expression was observed in both the nucleus and cytoplasm in colorectal adenocarcinoma, whereas Pdcd4 was expressed in the nucleus in normal colonic epithelial cells. Loss or weak expression of Pdcd4 was identified in 44 cases (40.7%) of cancer cells. Pdcd4 expression was associated with an increase in the nodal and clinical stage (p=0.022 and p= 0.016, respectively). Nuclear sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…Low PDCD4 expression level was associated with advanced T category of urinary system cancers (OR 4.87, 95% CI 1.69–14.00) [17] and head and neck cancers (OR 2.15, 95% CI 1.10–4.19) [18]. However, PDCD4 expression level was not associated with the T category of digestive system cancers (OR 0.98, 95% CI 0.46–2.08) [15, 19]. There was no obvious evidence for an association between PDCD4 expression and the N category of head and neck cancers [20, 21], respiratory system cancers [22], and digestive system cancers [7, 15, 19, 23].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low PDCD4 expression level was associated with advanced T category of urinary system cancers (OR 4.87, 95% CI 1.69–14.00) [17] and head and neck cancers (OR 2.15, 95% CI 1.10–4.19) [18]. However, PDCD4 expression level was not associated with the T category of digestive system cancers (OR 0.98, 95% CI 0.46–2.08) [15, 19]. There was no obvious evidence for an association between PDCD4 expression and the N category of head and neck cancers [20, 21], respiratory system cancers [22], and digestive system cancers [7, 15, 19, 23].…”
Section: Resultsmentioning
confidence: 99%
“…However, PDCD4 expression level was not associated with the T category of digestive system cancers (OR 0.98, 95% CI 0.46–2.08) [15, 19]. There was no obvious evidence for an association between PDCD4 expression and the N category of head and neck cancers [20, 21], respiratory system cancers [22], and digestive system cancers [7, 15, 19, 23]. Low PDCD4 level was associated with advanced M category of urinary system cancers (OR 4.87, 95% CI 1.69–14.00) [17] and advanced clinical stage of head and neck cancers (OR 2.30, 95% CI 1.44–3.69) [18, 20, 21, 24].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, CD133/CXCR4 cells were higher in sunitinib treated patients comparing untreated patients. The presence of CD133+ cells in the tumor also showed a prognostic value [50]. To test the hypothesis of SCLCCs existence in RCC, we began to explore whether these two selected subpopulations (CD105+ and CD133+ cells) were also present in established renal cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Bruno et al (2006) demonstrated that CD133 + progenitor cells derived from human RCC contributed to tumor vascularization. High expression of CD133 is associated with a macro-/micro-cystic pattern, non-metastatic disease, and non-sarcomatoid changes (Kim et al, 2011). CD133 may have a role in risk stratification; its overexpression was associated with longer survival in patients with ccRCC.…”
Section: Stem Cell Surface Markers In Renal Cscsmentioning
confidence: 99%